2001
DOI: 10.1159/000054752
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors in Cerebral Aging and Dementia: Epidemiological Arguments for a Role of Oxidative Stress

Abstract: There is increasing evidence that oxidative stress is involved in cerebral aging and dementia. The objective of this review is to give a progress report on the more recent results of the various epidemiologic cohorts studied for the association between nutrition of older people, the evolution of cognitive performances and the risk of later occurrence of dementia or stroke. The oxidative theory of pathological brain ageing is supported by animal laboratory experiments. Furthermore, experimental research has con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 86 publications
2
56
0
Order By: Relevance
“…Two recent studies have reported an association between adherence to a Mediterranean diet and risk of cognitive decline and dementia (Feart et al, 2009;Scaremas et al, 2009), whereas other studies have supported the possibility that vegetable consumption could help to maintain cognitive ability after age 70 years (Kang et al, 2005;Morris et al, 2006). One suggested mechanism for this is protection against free-radical induced-damage due to antioxidants, such as carotenoids and vitamin E (Deschamps et al, 2001), although intervention studies with supplements of these nutrients have found little evidence for beneficial effects of these nutrients (Yaffe et al, 2004;Wolters et al, 2005;Kang et al, 2006;Maylor et al, 2006;Grodstein et al, 2007;Jack et al, 2008). A number of other studies have explored possible association between B vitamins, particularly folate, and cognitive decline, as B vitamins are known to influence homocysteine levels, which in turn are associated with vascular disease (Seshadri et al, 2002;Clarke, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have reported an association between adherence to a Mediterranean diet and risk of cognitive decline and dementia (Feart et al, 2009;Scaremas et al, 2009), whereas other studies have supported the possibility that vegetable consumption could help to maintain cognitive ability after age 70 years (Kang et al, 2005;Morris et al, 2006). One suggested mechanism for this is protection against free-radical induced-damage due to antioxidants, such as carotenoids and vitamin E (Deschamps et al, 2001), although intervention studies with supplements of these nutrients have found little evidence for beneficial effects of these nutrients (Yaffe et al, 2004;Wolters et al, 2005;Kang et al, 2006;Maylor et al, 2006;Grodstein et al, 2007;Jack et al, 2008). A number of other studies have explored possible association between B vitamins, particularly folate, and cognitive decline, as B vitamins are known to influence homocysteine levels, which in turn are associated with vascular disease (Seshadri et al, 2002;Clarke, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, tea contains antioxidant flavonoids [Mukamal 2002]. Antioxidants may reduce mortality by decreasing the incidence of cardiovascular disease [Steinberg 2002], cancer [van Poppel 1997] and dementia [Deschamps 2001]. …”
Section: Introductionmentioning
confidence: 99%
“…Experimental research has consistently suggested that diet-related factors play an important role in cognitive functions in ageing. In humans, a number of epidemiological case -control and prospective studies analysed the association between nutrition, particularly fatty acids and antioxidant molecules (vitamins A, E and C, b-carotene and polyphenols) and cognition and risk of stroke (49) . In fact, intensive research has indicated that subclinical deficiencies of essential nutrients such as antioxidants (vitamins C and E), b-carotene, vitamin B 12 , vitamin B 6 and folate in combination with nutrition-related disorders, such as hypercholesterolaemia, hypertriacylglycerolaemia, hypertension and diabetes, are important risk factors associated with cognitive impairment (8) .…”
mentioning
confidence: 99%